THE USE OF TASK-BASED LANGUAGE INSTRUCTION THROUGH ONLINE VIDEO TELECONFERENCE APPLICATION IN TEACHING SPEAKING SKILL ON ENGLISH DEPARTMENT STUDENTS OF NAHDLATUL ULAMA UNIVERSITY - Nailul Authar; Mujad Didien Afandi (Universitas Muhammadiyah Makassar, 2020)
Instruction deals with something that we ask someone to do something. It is also related to approach when we talk about educational area. Task – Based Language Instruction is an approach that in relation with student-centred approach to second language instruction. Young generation in the millennial era 4.0, nowadays, are born in the middle of complete facilities. Everything becomes easier in their life, communication, and education. Moreover, they are supported by good infrastructure of technology. Google, YouTube, Vlog, Website, Media social are tools that support their academic process. This research belonged to qualitative research. Thus, the qualitative method was chosen for this study because it was appropriate with the focus of this research. The data in this study were in the form of utterances produced by the students of English Department of Unusa University which were obtained from observing the teaching learning process and from the interview through online video application. According to the result, there are two benefits that using Task Based Instruction through online video application in teaching speaking skill. Firstly, it can build more on students’ confidence; secondly, they can develop their speaking skill by collaborating many vocabularies they know. In conclusion, of the use Task Based Instruction, it is the best way for students and lecture in teaching and learning process especially in teaching speaking skill.